2017
DOI: 10.1073/pnas.1703663114
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the peptide-modifying radical SAM enzyme SuiB elucidate the basis of substrate recognition

Abstract: Posttranslational modification of ribosomally synthesized peptides provides an elegant means for the production of biologically active molecules known as RiPPs (ribosomally synthesized and posttranslationally modified peptides). Although the leader sequence of the precursor peptide is often required for turnover, the exact mode of recognition by the modifying enzymes remains unclear for many members of this class of natural products. Here, we have used X-ray crystallography and computational modeling to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 38 publications
(75 reference statements)
4
134
0
Order By: Relevance
“…73 The Seyedsayamdost and Ando labs solved the crystal structure of SuiB (a close ortholog of StrB) from Streptococcus suis . 74 SuiB uses the precursor peptide SuiA, a homolog of StrA (Fig. 12), as a substrate.…”
Section: The Spasm–twitch Familymentioning
confidence: 99%
See 2 more Smart Citations
“…73 The Seyedsayamdost and Ando labs solved the crystal structure of SuiB (a close ortholog of StrB) from Streptococcus suis . 74 SuiB uses the precursor peptide SuiA, a homolog of StrA (Fig. 12), as a substrate.…”
Section: The Spasm–twitch Familymentioning
confidence: 99%
“…While the SuiA core peptide is disordered in the structure, computer simulation of the core peptide structure suggested that the binding mode of the leader peptide is consistent with positioning of the core sequence in the SuiB active site. 74 Thus, binding of the leader peptide to the catalytic barrel of SuiB, rather than its RRE domain, is likely relevant to SuiB catalysis.…”
Section: The Spasm–twitch Familymentioning
confidence: 99%
See 1 more Smart Citation
“…1) [29][30][31]. Streptide is a new family of RiPPs that are biosynthesized via a short pathway containing three genes: strA, which encodes the precursor peptide, strB, a radical S-adenosylmethionine (SAM) enzyme, and strC, an ABC transporter [32][33][34][35]. The strB enzyme is responsible for the formation of the unusual lysine-to-tryptophan crosslink.…”
Section: Selection Of the Shp/rgg Quorum Sensing System As An Inquirymentioning
confidence: 99%
“…The precursor peptide binds in a cleft between the third alpha helix (α3) and the third beta strand (β3), forming an ordered, fourstranded, antiparallel beta sheet ( Figure S1). RRE domains can exist either as a discretely encoded protein (<100 residues) or as a fusion to a larger protein domain [6][7][8][9][10] . All RREs share sequence similarity to PqqD, which is a protein involved in pyrroloquinoline quinone (PQQ) cofactor synthesis-a redox cofactor produced by many prokaryotes 11 .…”
Section: Introductionmentioning
confidence: 99%